Thiophene-containing thiolato dimers, oxygen inserted Cu(II) complex, crystal structures, molecular docking and theoretical studies. Issue 11 (2nd July 2016) - Mobin, Shaikh M.; Tauqeer, Mohd.; Mohammad, Akbar; Mishra, Veenu; Kumari, Pratibha
Abstract: Reactions of n -butyl- and n -octyl-thiophene with CS2 at 0 °C resulted in thiolate dimers1 and2, respectively. The reaction of1 with Cu(NO3 )2 ·3H2 O in methanol under ambient reaction conditions yielded monomeric [Cu II {( n -C4 H9 (C4 H2 S)CS2 O}2 ] (3 ).1 and3 were authenticated by their single-crystal X-ray crystal structures. Crystal structure of3 revealed cleavage of the S-S bond of1 followed by insertion of O-atom, forming a new five-membered Cu–O–S–C–S metallacycle.1, 2, and3 were further investigated for their bioactivity through molecular docking with nine different proteins having medicinal implications. Molecular docking of1, 2 and3 revealed considerable interaction with different proteins viz. cancer protein Tankyrase 2, influenza viral protein Polymerase subunit PAC –PB1N complex (H5N1), Polymerase subunit PA endonuclease (H1N1), Polymerase subunit PAn Apo(avian influenza), and FTSZ ( Bacillus subtilis ). Comparatively, 1 has promising application in therapeutics as compared to2 and3 based on its inhibitory constant and binding energy. Density functional theory calculations were performed to better understand the bonding of complex using MO diagram in1–3 . Moreover, TDDFT calculations were performed to facilitate the assignment of electronic transitions of UV–Vis spectra. Abstract :